Investigating an outbreak of equine viral arteritis at two connected premises. (7th December 2020) - Lattimer, Joseph; Roberts, Helen; Barnard, Matt; Paterson, Andy; Bell, Iain; Hepple, Richard; Holland, Sam; George, Alastair
Abstract : In early 2019, four stallions in the south of England tested positive for equine viral arteritis following routine prebreeding screening. Here, a team from Defra and the APHA describe the epidemiological investigation that was carried out to determine the origin of infection and the potential for its transmission across the country.